Synergistic Catalytic Oxidation of Ethylbenzene to Acetophenone by Metallophthalocyanine Intercalated Layered Double Hydroxide with Oxygen. Issue 2 (9th January 2018) - Zhou, Weiyou; Dai, Xuan; Chen, Yong; Sun, Fu'an; He, Mingyang; Chen, Qun
Abstract: The organic‐inorganic hybrid material originated from metallophthalocyanine and layered double hydroxide has been identified as bifunctional catalyst for the oxidation of ethylbenzene to acetophenone. The hybrids exhibited excellent catalytic activity in the selective oxidation through O2 /NHPI (N‐hydroxyphthalimide) system with excellent selectivity of acetophenone. The hybrid could accelerate not only the formation of hydroperoxide, but also the decomposition of hydroperoxide. Further, the catalyst also exhibited high activity in the transformation of 1‐phenylethanol to acetophenone. The present catalytic system could also catalyze the aerobic oxidation of varied alkyl arenes under the optimized reaction conditions. A series of controlled experiments suggested that the basicity of the hybrid benefited for the catalytic activity, and synergistic effect might exist between the basicity and the activity of metallophthalocyanine during the oxidation. On the basis of obtained results and Hammett experiment, a possible mechanism of the oxidation of ethylbenzene under the hybrid in the presence O2 /NHPI has been proposed. Abstract : The organic‐inorganic hybrid material originated from metallophthalocyanine and layered double hydroxide has been identified as efficient catalyst for the oxidation of ethylbenzene to acetophenone.